The Effect Of Giving Bangun-Bangun Leaf Vegetables On The Smooth Breastfeeding Of Breastfeeding Mothers At The Satria Health Center, Bagelen Village, Padang Hilir District In 2023 - Rangkuti, Saddiyah; Zaen, Niasty Lasmy (Jurnal EduHealth, 2024)
Breastfeeding is one of the first steps for a human being to get a healthy life. Breastfeeding is done by a mother by giving exclusive breastfeeding for at least until the child is 6 months old up to 2 years. One way that can be used to facilitate breast milk is to eat vegetables of bangun-bangun leaves. The purpose of this study is to determine the effect of giving bangun-bangun leaves vegetables on the smoothness of breast milk in breastfeeding mothers at the Satria Health Center, Bagelen Village, Padang Hilir District in 2023. This type of research is a pre-experimental design with a one group pre-test and post-test design approach. The population of this study was all breastfeeding mothers with infant age 0-6 months who were in the Satria Health Center, Bagelen Village, Padang Hilir District, which was as many as 20 people. The sampling technique takes the total population, namely all breastfeeding mothers in March 2023, which is 20 people. The results of the research showed that through statistical tests using the Wilcoxon test, a p-value of 0.000 (p-value <0.05) was obtained for the variable giving bangun-bangun leaves vegetables. The conclusion is that there is a significant influence between the effect of giving bangun-bangun leaves vegetables on the smoothness of breast milk in breastfeeding mothers at the Satria Health Center, Bagelen Village, Padang Hilir District in 2023. It is recommended for mothers who have problems with milk production to be able to use wake-up leaves as food to launch milk production.